Моделювання плоско-паралельного руху спеціалізованого ширококолійного агрозасобу для колійної системи землеробства - Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Kuvachov, Volodymyr (ТДАТУ, 2016)
Presents the results of theoretical studies modeling the motion of a wide span tractor for controlled traffic farming in the horizontal and vertical plane with different ways of its management.
Keywords: Controlled Traffic Farming; Wide Span Tractor; theoretical modeling